Clinical Management of Stable Coronary Artery Disease in Patients With Type 2 Diabetes Mellitus: A Scientific Statement From the American Heart Association. Issue 19 (12th May 2020) - Arnold, Suzanne V.; Bhatt, Deepak L.; Barsness, Gregory W.; Beatty, Alexis L.; Deedwania, Prakash C.; Inzucchi, Silvio E.; Kosiborod, Mikhail; Leiter, Lawrence A.; Lipska, Kasia J.; Newman, Jonathan D.; Welty, Francine K.
Abstract : Although cardiologists have long treated patients with coronary artery disease (CAD) and concomitant type 2 diabetes mellitus (T2DM), T2DM has traditionally been considered just a comorbidity that affected the development and progression of the disease. Over the past decade, a number of factors have shifted that have forced the cardiology community to reconsider the role of T2DM in CAD. First, in addition to being associated with increased cardiovascular risk, T2DM has the potential to affect a number of treatment choices for CAD. In this document, we discuss the role that T2DM has in the selection of testing for CAD, in medical management (both secondary prevention strategies and treatment of stable angina), and in the selection of revascularization strategy. Second, although glycemic control has been recommended as a part of comprehensive risk factor management in patients with CAD, there is mounting evidence that the mechanism by which glucose is managed can have a substantial impact on cardiovascular outcomes. In this document, we discuss the role of glycemic management (both in intensity of control and choice of medications) in cardiovascular outcomes. It is becoming clear that the cardiologist needs both to consider T2DM in cardiovascular treatment decisions and potentially to help guide the selection of glucose-lowering medications. Our statement provides a comprehensive summary of effective, patient-centered management of CAD in patients with T2DM, with emphasis on the emerging evidence. Given the increasing prevalence of T2DM and the accumulating evidence of the need to consider T2DM in treatment decisions, this knowledge will become ever more important to optimize our patients' cardiovascular outcomes.